1975
DOI: 10.1088/0022-3727/8/15/013
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion profiles of zinc in indium phosphide

Abstract: A series of experiments is described in which radio-tracer Zn was diffused into n-type InP over a wide range of experimental conditions. Diffusions were carried out in the temperature range 650-900 "C, for varying times of diffusion, and for a varicty of ambient vapour pressures. Both chemical and isoconcentration diffusions were performed, and it was found that the diffusion constants for chemical diffusion are much smaller than those for isoconcentration experiments. A detailed consideration of the shapes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(42 citation statements)
references
References 13 publications
3
39
0
Order By: Relevance
“…Although the p r e g r o w t h duration in which ramp cooling took place ranged from 10 to 30 min, we have used 20 min as the median value in the calculation. The values of Dzn are obtained to be 3.5 • 1.0 X 10 -1~ cm 2 sec -1 for the diffusion from the vapor in the temperature range of 620~176 and 1.0 _ 0.3 X 10 -l~ cm 2 sec -1 for the diffusion from the liquid in the t e m p e r a t u r e range of 620~176 Taking into account the Zn evaporation continuously occurring during the growth and also the appreciable variation of the initial Zn fraction in the melt, these values are considered to be in a reasonable agreement with earlier works (10,11).…”
Section: Resultssupporting
confidence: 87%
“…Although the p r e g r o w t h duration in which ramp cooling took place ranged from 10 to 30 min, we have used 20 min as the median value in the calculation. The values of Dzn are obtained to be 3.5 • 1.0 X 10 -1~ cm 2 sec -1 for the diffusion from the vapor in the temperature range of 620~176 and 1.0 _ 0.3 X 10 -l~ cm 2 sec -1 for the diffusion from the liquid in the t e m p e r a t u r e range of 620~176 Taking into account the Zn evaporation continuously occurring during the growth and also the appreciable variation of the initial Zn fraction in the melt, these values are considered to be in a reasonable agreement with earlier works (10,11).…”
Section: Resultssupporting
confidence: 87%
“…Conibeer et al [9] found that adding Sb to Zn source can shorten the p-n junction depth by decreasing the diffusivity because that Zn diffusivity is inversely proportional to the Sb vapor pressure. Similar results have been reported in GaAs [19], GaP [18], and InP [20,21]. In addition to Zn and Zn-Sb sources, Zn-Ga was often used as a diffusion source [8,12].…”
Section: Introductionsupporting
confidence: 75%
“…The multiplication layer is intrinsic in theory, but the Zn concentration of the p+InP layer is an error function distribution in the thermal diffusion process [7],which is equivalent to changing the dopant concentration of the multiplication layer,or even introducing traps to the interface between multiplication layer and p+InP layer. We change the doping concentration of multiplication layer from 1E15 cm -3 to 4E16 , as seen in Fig.…”
Section: (A) Doping Concentrationmentioning
confidence: 99%